Alloy for manufacturing tools for manufacturing aeronautical components made of composite material

Through the use of new alloys, the problems of thermal expansion mismatch and insufficient mechanical strength of composite aviation component tools in additive manufacturing are solved, and high productivity and high-quality component manufacturing are achieved, ensuring the thermal expansion compatibility between the tool and composite materials and Resistance to melt pool collapse.

CN119256104APending Publication Date: 2025-01-03APERAM
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202280096461.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing alloys used to manufacture composite aviation components tools during additive manufacturing due to mismatched thermal expansion and insufficient mechanical strength, resulting in low productivity and poor component quality, especially collapse under reused tools at high temperatures. .

Method used

A new alloy is used, containing 32.6%~38.0% nickel, 0.80%~4.20% cobalt, 1.0%~2.0% titanium, 0.0010%~0.0500% rare earth elements, 0.10%~0.35% silicon, 0.15% ~0.60% manganese, 0.005%~0.04% carbon, the balance is iron and impurities. The filler wire is made through hot processing and wire drawing steps. It is used as a filler material in metal additive manufacturing process to ensure 20℃ to 200 The average thermal expansion coefficient between °C is in the range of 2.2×10-6°C-1 to 2.9×10-6°C-1.

Benefits of technology

Achieves thermal expansion compatibility with composite materials, improves the mechanical strength and vacuum sealing of the tool, enhances the anti-pool collapse capability of the tool at high temperatures, allowing high productivity (deposition rate above or equal to 450 cubic centimeters/hour) And excellent quality parts manufacture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256104A_ABST
    Figure CN119256104A_ABST
Patent Text Reader

Abstract

The invention relates to an alloy for manufacturing a tool for manufacturing an aeronautical component made of a composite material, the alloy comprising, by weight: 32.6% < = nickel < = 38.0%; 0.80% < = cobalt < = 4.20%, where cobalt > =-1.00 * nickel% + 36.80%, where nickel% represents the nickel content in the alloy by weight percent, and cobalt < =-1.63 * nickel% + 62.72%, where nickel% represents the nickel content in the alloy by weight percent; 1.0% < = titanium < = 2.0%; 0.0010% < = rare earth element < = 0.0500%; 0.10% < = silicon < = 0.35%; 0.15% < = manganese < = 0.60%; 0.005% < = carbon < = 0.04%; and the balance of iron and impurities produced by the production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an alloy for the manufacture of tools, in particular moulds or mould parts, intended for the manufacture of composite aerospace parts. Background Art

[0002] The search for a trade-off between weight and mechanical properties in the aviation industry has led to the production of increased amounts of composite materials for aviation parts (particularly structural parts or functional components such as wings or fuselages). These composite materials typically comprise a polymer matrix in which reinforcing fibers are embedded. For example, the polymer matrix is ​​formed by a thermosetting resin, particularly an epoxy resin, a polyester resin, a vinyl ester resin, a polyamide resin or a phenolic resin. For example, the reinforcing fibers may be selected from glass fibers, carbon fibers, Kevlar fibers, aluminum fibers or titanium fibers. In some cases, the braided fibers are used to further improve the mechanical properties of the components.

[0003] For the production of these components, the starting material is usually a prepreg, i.e. a strip-shaped composite material containing reinforcing fibers embedded in a polymer matrix. The component is manufactured from this starting material using one of two methods:

[0004] (a) Lamination and autoclave curing, comprising the following consecutive steps:

[0005] a. depositing the starting material in successive layers on a convex or concave metal mold to obtain a layer on the metal mold;

[0006] b. vacuum packaging the above laminate to remove air bubbles and pressing the laminate into a more or less complex shape of the mold;

[0007] c. curing the polymer matrix of the composite material by heat treating the assembly comprising the mold and the layup for several hundred minutes under pressure at a temperature between 120°C and 180°C in an autoclave;

[0008] (b) Compression molding, which is similar to method (a), but instead of the autoclave curing step, includes a curing step of the composite material in a press, the curing step being performed by hot pressing the laminate between a first mold, the laminate being coated on the first mold, and a second mold having a cavity matching the first mold. The hot pressing is performed at a temperature and for a time similar to that described in method (a).

[0009] Therefore, the tooling used to manufacture composite aerospace components by the above method must ideally have the following properties:

[0010] Good mechanical strength at the curing temperature of the polymer matrix and under the extensive thermal cycles resulting from repeated tool use;

[0011] A coefficient of thermal expansion that matches that of the composite material used;

[0012] Dimensional stability;

[0013] Vacuum tightness.

[0014] Furthermore, the tool must enable the production to be carried out at the lowest cost, particularly in terms of manufacturing cost, final weight, manufacturing time, etc.

[0015] For the manufacture of parts made of composite materials containing carbon fibers embedded in an epoxy resin matrix, if the metal alloy used to make the tool has a coefficient of thermal expansion between 20°C and 200°C of 2.2×10 -6 ℃ -1 and 2.9×10 -6 ℃ -1 If the thermal expansion coefficient of the tool is between 0.01 and 0.08, then it is considered that the thermal expansion coefficient of the tool is compatible with the thermal expansion coefficient of the composite material used.

[0016] Invar M93 has a coefficient of thermal expansion suitable for the manufacture of such tools. In addition, it also exhibits some excellent properties for the above-mentioned applications, especially in terms of scratch and impact resistance, increased tool life compared to non-metallic molds, the possibility of obtaining machine-welded tool or mold structures, and the possible processing of tools with machine-welded structures.

[0017] In order to reduce the production costs and improve the productivity associated with producing tools for these applications, people are looking to produce such tools using additive manufacturing processes. Additive manufacturing enables rapid and flexible manufacturing of such tools. It also enables the production of tools that can withstand more thermal cycles with limited maintenance.

[0018] To further improve productivity, one seeks to achieve relatively high deposition rates in additive manufacturing processes, such as deposition rates greater than or equal to about 450 cubic centimeters per hour.

[0019] One method of increasing deposition rates in additive manufacturing is to reduce the time between two consecutive material deposition passes, also referred to as inter-pass time in the remainder of this document. However, the inventors of the present disclosure have determined that when test walls were manufactured by arc wire additive manufacturing using Invar M93 wire, a reduction in inter-pass time resulted in collapse of these walls due to an increase in inter-pass temperature. In particular, the inventors observed that the walls began to sag when the inter-pass temperature reached 600°C and above. Therefore, the method was unable to produce parts with satisfactory quality at the target production rate. Summary of the invention

[0020] One object of the present invention is to propose an alloy that enables the additive manufacturing of tools intended for the manufacture of aerospace components in composite materials with improved productivity.

[0021] For this purpose, the invention relates to an alloy for making a tool intended for making aerospace parts in composite material, comprising, by weight:

[0022] 32.6%≤Nickel≤38.0%;

[0023] 0.80% ≤ Cobalt ≤ 4.20%, and:

[0024] Cobalt ≥ -1.00 × Ni% + 36.80%, wherein Ni% represents the nickel content in the alloy in percentage by weight, and

[0025] Cobalt ≤ -1.63×Ni%+62.72%, wherein Ni% represents the nickel content in the alloy in percentage by weight;

[0026] 1.0%≤Titanium≤2.0%;

[0027] 0.0010%≤Rare earth elements≤0.0500%;

[0028] 0.10%≤Silicon≤0.35%;

[0029] 0.15%≤Manganese≤0.60%;

[0030] 0.005%≤Carbon≤0.04%;

[0031] The balance is iron and impurities resulting from the production process.

[0032] Preferably, the impurities generated by the production process include by weight:

[0033] Calcium ≤ 0.0015%;

[0034] Magnesium ≤ 0.0035%;

[0035] Aluminum ≤ 0.0085%;

[0036] Oxygen ≤ 0.0025%;

[0037] Sulfur ≤ 0.0035%;

[0038] Phosphorus ≤ 0.0100%;

[0039] Boron ≤ 0.0005%;

[0040] Molybdenum ≤ 0.1%;

[0041] Chromium ≤ 0.1%;

[0042] Copper ≤ 0.1%;

[0043] Niobium ≤ 0.01%;

[0044] Vanadium ≤ 0.01%.

[0045] Preferably, the rare earth element includes yttrium, cerium, lanthanum, neodymium, praseodymium or a mixture thereof.

[0046] The invention also relates to a filler wire made of the alloy defined above.

[0047] The present invention also relates to a method for producing a filler wire as defined above, the method comprising the following steps:

[0048] Providing a semi-finished product of the alloy as described above;

[0049] thermally processing the semi-finished product to form an intermediate filament; and

[0050] The intermediate wire is processed into a filler wire having a smaller diameter than the intermediate wire, the processing comprising a wire drawing step.

[0051] The invention also relates to the use of an alloy as defined above for manufacturing at least a portion of a tool for manufacturing aerospace components in composite material.

[0052] The invention also relates to a component or a part of a component made of the alloy defined above.

[0053] According to the specific characteristics of the component or part of a component:

[0054] The component or a part of the component is obtained by metal additive manufacturing;

[0055] The component in question is a tool, in particular a mould, intended for the manufacture of a composite aerospace component.

[0056] The present invention also relates to a method for manufacturing a component or a part of a component, comprising the steps of manufacturing the component or the part of a component by a metal additive manufacturing process using a filler wire made of the alloy defined above and / or a powder of the alloy defined above as filler material.

[0057] According to the specific characteristics of the manufacturing method:

[0058] The additive manufacturing process is selected from arc wire, laser wire, electron beam wire, and a hybrid additive manufacturing process combining the techniques of arc wire and powder laser or arc wire and laser wire.

[0059] The present invention also relates to the use of a filler wire as defined above as a filler wire in a metal additive manufacturing process.

[0060] The invention also relates to a metal powder made from the alloy defined above.

[0061] The present invention also relates to a method for producing the metal powder defined above, the method comprising the steps of: providing a filler wire material defined above, and plasma atomizing the filler wire material to obtain the metal powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] The invention will be better understood on reading the following description given by way of example only and with reference to the accompanying drawings, in which:

[0063] Figure 1 a graph showing the permissible range of cobalt content in the alloy of the present invention as a function of the nickel content in the alloy, the content being expressed as weight percent; and

[0064] Figure 2 is a schematic perspective view of a component obtained by additive manufacturing according to the present invention. DETAILED DESCRIPTION

[0065] The alloy of the present invention comprises, by weight:

[0066] 32.6%≤Nickel≤38.0%;

[0067] 0.80% ≤ Cobalt ≤ 4.20%, and:

[0068] Cobalt ≥ -1.00 × Ni% + 36.80%, where Ni% represents the nickel content in the alloy in percentage by weight, and

[0069] Cobalt ≤ -1.63×Ni%+62.72%, where Ni% represents the nickel content in the alloy by weight percentage;

[0070] 1.0%≤Titanium≤2.0%;

[0071] 0.0010%≤Rare earth elements≤0.0500%;

[0072] 0.10%≤Silicon≤0.35%;

[0073] 0.15%≤Manganese≤0.60%;

[0074] 0.005%≤Carbon≤0.04%;

[0075] The balance is iron and impurities resulting from the production process.

[0076] The so-called impurities generated by the production process refer to elements contained in the raw materials used to prepare the alloy or originating from the equipment used in the preparation process (such as furnace refractory materials). These residual elements have no metallurgical effect on the alloy.

[0077] In particular, the impurities generated by the production process include by weight:

[0078] Calcium ≤ 0.0015%;

[0079] Magnesium ≤ 0.0035%;

[0080] Aluminum ≤ 0.0085%;

[0081] Oxygen ≤ 0.0025%;

[0082] Sulfur ≤ 0.0035%;

[0083] Phosphorus ≤ 0.0100%;

[0084] Boron ≤ 0.0005%;

[0085] Molybdenum ≤ 0.1%;

[0086] Chromium ≤ 0.1%;

[0087] Copper ≤ 0.1%;

[0088] Niobium ≤ 0.01%;

[0089] Vanadium ≤ 0.01%.

[0090] More particularly, the contents of sulfur, phosphorus, oxygen, boron, magnesium, aluminum and calcium are preferably limited to the above upper limits to prevent the alloy's weldability from being reduced. In particular, the contents of magnesium, aluminum, calcium and oxygen are limited to the above specified contents to prevent a reduction in arc stability in arc mode (particularly in additive manufacturing). The contents of sulfur, phosphorus and boron are limited to the above contents to prevent a reduction in the hot cracking resistance of parts made of the alloy.

[0091] Finally, the contents of molybdenum, chromium, copper, niobium and vanadium are preferably limited to the amounts noted above to prevent a decrease in the alloy's coefficient of thermal expansion.

[0092] The above alloy is an Invar type alloy.

[0093] The alloy of the present invention is an austenitic alloy at a temperature equal to ambient temperature (about 20° C.).

[0094] The average thermal expansion coefficient of the alloy of the present invention between 20°C and 200°C is α 20℃_200℃ Between 2.2×10 -6 ℃ -1 and 2.9×10 -6 ℃ -1When the alloy of the present invention is used in accordance with the above method for the manufacture of tools intended for the manufacture of aerospace parts made of composite materials, in particular epoxy resin matrices containing embedded reinforcing fibers, an average thermal expansion coefficient in this range between 20°C and 200°C is advantageous. The coefficient ensures compatibility in terms of thermal expansion between tools made of the above alloys and composite materials used to manufacture aerospace parts. Any lack of compatibility between the average thermal expansion coefficients of tools and parts may lead to the risk of distortion or deformation of the parts during the manufacturing process due to the expansion of the parts relative to the tools, or to the risk of stress generation inside the parts during the cooling process after the curing process. In addition, the composite material may fall off the tool during heating, produce drips and expose the fibers, resulting in the formation of faulty parts. Therefore, using the alloy of the present invention, it is possible to obtain composite parts for aerospace applications, in particular composite parts containing epoxy resin matrices in which carbon reinforcing fibers are embedded, which meet the theoretical dimensions and have fibers that are fully protected by the resin without residual stress.

[0095] In addition, the temperature range between 20°C and 200°C is 2.2×10 -6 ℃ -1 and 2.9×10 -6 ℃ -1 The average thermal expansion coefficient α 20℃_200℃ Ensures good dimensional stability.

[0096] Furthermore, the alloy of the invention makes it possible to obtain parts such as tools or parts of tools for the production of aerospace parts, having:

[0097] Good mechanical strength at the curing temperature of the polymer matrix and under the extensive thermal cycles resulting from repeated tool use; and

[0098] Vacuum tightness.

[0099] In the alloy of the invention, the nickel content is between 32.6% and 38.0% by weight. If the nickel content is below 32.6% by weight, there is a risk of martensitic transformation at temperatures close to ambient temperature and of the alloy no longer being austenitic at ambient temperature, which is detrimental to its dimensional stability. If the nickel content is above 38.0% by weight, the thermal expansion coefficient of the alloy becomes too high, so that the dimensional stability of the alloy is impaired.

[0100] In the present invention, the cobalt content is between 0.80 wt % and 4.20 wt %, and also satisfies the following conditions: cobalt ≥ -1.00×nickel%+36.80% and cobalt ≤ -1.63×nickel%+62.72%. In these inequalities, nickel% represents the nickel content in the above alloy in weight percentage, and cobalt% represents the cobalt content in the above alloy in weight percentage.

[0101] The permissible range of cobalt content expressed as a percentage by weight varies with the nickel content as follows: Figure 1 In this figure:

[0102] The equation for the straight line C_sup is: Co = 4.20%

[0103] The equation for the straight line C_inf is: Co = 0.80%

[0104] The equation of line C1 is: Cobalt = -1.00 × Nickel% + 36.80%

[0105] The equation of straight line C2 is: Cobalt = -1.63 x Nickel % + 62.72%.

[0106] In this figure, the scope of the present invention corresponds to the range defined by straight lines C1, C2, C_inf, and C_sup.

[0107] The cobalt content within this range can achieve a temperature between 20°C and 200°C of 2.2×10 -6 ℃ -1 and 2.9×10 -6 ℃ -1 The average thermal expansion coefficient between.

[0108] If the cobalt content is higher than 4.20% by weight, corresponding to Figure 1 For the cobalt content above the straight line C_sup, the average thermal expansion coefficient between 20°C and 200°C is lower than the lower limit of 2.2×10- -6 ℃ -1 Also, in this case, the risk of a martensitic transformation occurring during work hardening, in particular by plastic deformation (e.g. during wire drawing), increases, which would increase the cost price of the manufacturing method by wire drawing and require intermediate austenite annealing to an intermediate wire diameter of, for example, about 2 mm.

[0109] If the cobalt content is less than 0.80% by weight, corresponding to Figure 1 For the cobalt content below the straight line C_inf, the average thermal expansion coefficient between 20°C and 200°C is higher than the upper limit of 2.9×10 -6 ℃ -1 risk.

[0110] If the cobalt content is below the straight line C1, that is, when cobalt <-1.00×Ni%+36.80%, the average thermal expansion coefficient between 20°C and 200°C is higher than the upper limit of 2.9×10 -6 ℃ -1 risk.

[0111] If the cobalt content is above the straight line C2, that is, when cobalt>-1.63×Ni%+62.72%, the average thermal expansion coefficient between 20°C and 200°C is higher than the upper limit value of 2.9×10 -6 ℃ -1 risk.

[0112] In the alloy according to the invention, a titanium content of between 1.0 and 2.0 wt. % allows good resistance to melt pool collapse during additive manufacturing of components made of the alloy according to the invention by arc additive manufacturing, thereby preventing in particular the formation of droplets in the component.

[0113] If the titanium content is less than 1.0 wt. %, during additive manufacturing (especially arc additive manufacturing) of parts with the alloy of the present invention, the ability to resist melt pool collapse is insufficient, and high production rates (especially deposition rates greater than or equal to 450 cubic centimeters / hour) will produce unwanted droplets.

[0114] If the titanium content is higher than 2.0 wt%, the average thermal expansion coefficient between 20°C and 200°C is higher than the upper limit of 2.9×10 -6 ℃ -1 risk.

[0115] In the alloy of the present invention, the content of rare earth elements is between 0.0010% and 0.0500%. The addition of rare earth elements at a specified content can enhance the effect of titanium, thereby improving the resistance to molten pool collapse during the additive manufacturing (especially arc additive manufacturing) process of the alloy component of the present invention.

[0116] The above-mentioned rare earth elements are particularly selected from yttrium, cerium, lanthanum, neodymium and praseodymium or mixtures thereof.

[0117] In one embodiment, the rare earth element is yttrium.

[0118] In one variant, the rare earth element comprises a mixture of cerium and lanthanum and originates, for example, from a mischmetal. In particular, the rare earth element is a mixture of cerium and lanthanum.

[0119] In the alloy of the present invention, silicon, manganese and carbon are added for desulfurization and deoxidation of the alloy. Their contents by weight are selected from the following ranges:

[0120] 0.10%≤Silicon≤0.35%

[0121] 0.15%≤Manganese≤0.60%

[0122] 0.005%≤Carbon≤0.04%

[0123] If the silicon and / or manganese content is higher than the limits given above, the thermal expansion coefficient has a value higher than the upper limit of 2.9×10 -6 ℃ -1 risk.

[0124] Carbon contents above 0.04% run the risk of causing hot cracking problems during solidification due to precipitation of titanium carbides, resulting in poor performance of the weld metal during solidification.

[0125] The alloy of the invention is advantageous. It allows high-quality tools or parts of tools for manufacturing aerospace parts made of composite materials, in particular epoxy resin matrices containing embedded carbon fibers as reinforcing fibers, to be produced in a simple, flexible and highly productive manner by additive manufacturing. The alloy has the desired properties of the above alloys, in particular having a relative humidity of 2.2×10 -6 ℃ -1 and 2.9×10 -6 ℃ -1 The average thermal expansion coefficient between 200 and 200 mm / s, which results in satisfactory compatibility between the tool and the part to be manufactured, as well as good resistance to melt pool collapse during the additive manufacturing of the part, allowing the production of high-quality parts at high productivity (in particular, deposition rates greater than or equal to 450 cm3 / h).

[0126] The alloys described in the present invention can be prepared by any suitable method known to those skilled in the art.

[0127] For example, in the first step, starting materials are placed in an electric arc furnace. These starting materials are melted in the electric arc furnace and then vacuum oxygen decarburization (VOD) is performed in a conventional manner using a new vacuum oxygen decarburization vessel to obtain:

[0128] Decarburization by oxygen injection and vacuum pumping (a few mbar);

[0129] Deoxidation and desulfurization on lime-based slag; and

[0130] Adjustment of silicon content.

[0131] The invention also relates to a filler wire made of the alloy having the composition defined above.

[0132] The filler wire is particularly suitable for use as a filler wire in a metal additive manufacturing process.

[0133] For example, the above-mentioned additive manufacturing process is an additive manufacturing process that uses an electric arc, a laser beam and / or an electron beam as an energy source to obtain fusion of the filler wire.

[0134] In particular, the aforementioned additive manufacturing process is an additive manufacturing process known as directed energy deposition, in which a filler material is deposited, in particular through a nozzle, and is immediately melted by concentrated thermal energy, in particular by a laser beam, electron beam and / or electric arc.

[0135] For example, the aforementioned additive manufacturing process is an arc wire (arc additive manufacturing or WAAM process), a laser wire or an electron beam wire (electron beam freeform manufacturing or electron beam additive manufacturing) process, or a hybrid additive manufacturing process combining arc wire and powder laser or arc wire and laser wire technology.

[0136] For the hybrid arc wire and powder laser process, the powder used has the same composition as the wire.

[0137] The powder, after sieving, has a particle size between 20 microns and 150 microns, for example, obtained from the filler wire of the present invention by using plasma atomization technology. Preferably, the filler wire used to make the above powder has a diameter of about 3 mm.

[0138] The particle size of the above powder is determined in particular by the following method. Batches of powder are separated into a plurality of particle size distributions using a stainless steel sieve under ultrasonic vibration. The particle size distribution analysis of the sieved powder is carried out according to standard ASTM B214-07. Sieving can obtain 5 levels of particle size: <20 microns, 20 microns to 45 microns, 45 microns to 75 microns, 75 microns to 105 microns, >105 microns.

[0139] The technique of preparing powders from filaments using plasma atomization techniques is known per se and will therefore not be described in greater detail.

[0140] The present invention also relates to a method for producing a filler wire of the above alloy.

[0141] The method comprises, in a first step, providing a semi-finished product made of this alloy. The alloy can be cast either as an ingot or directly in the form of a billet by continuous casting, in particular rotary continuous casting. Thus, the semi-finished product obtained after this step is advantageously an ingot or billet and has a diameter, for example, between 130 mm and 230 mm, more particularly about 150 mm.

[0142] The semi-finished product is transformed into an intermediate wire material through heat processing.

[0143] In particular, in this hot working step, the semi-finished product, in particular an ingot or billet, is reheated in a gas-fired furnace, for example to a temperature between 1180° C. and 1220° C.

[0144] It is then subjected to heat roughing to reduce its cross section, for example to give it a square cross section with a side length of about 100 to 200 mm. A semi-finished product with a reduced cross section is thus obtained. The length of the semi-finished product with a reduced cross section is between 10 and 20 meters.

[0145] The semi-finished product with reduced cross section is hot-worked again at a temperature between 950° C. and 1150° C. to obtain an intermediate wire. The intermediate wire can in particular be a wire rod. For example, it has a diameter between 5 mm and 21 mm, in particular about 5.5 mm. Advantageously, in this step, the intermediate wire is produced by hot rolling on a wire rod mill.

[0146] Optionally, the intermediate wire is subsequently heat treated in a gas furnace at a temperature of 1150° C. to 1220° C. for 60 minutes to 120 minutes, and then solution annealed.

[0147] The intermediate filament is then stripped and wound onto a spool.

[0148] Optionally, the intermediate wire material thus obtained is subjected to wire drawing on a wire drawing device of known type to obtain a filled wire material. The above-mentioned filled wire material has a smaller diameter than the starting wire material. In particular, it has a diameter between 0.5 mm and 3.5 mm. Advantageously, its diameter is between 0.8 mm and 2.4 mm.

[0149] The wire drawing step comprises one or more wire drawing passes according to the final diameter to be achieved, and preferably an annealing treatment is performed between two consecutive wire drawing passes. For example, the annealing is performed online at a temperature of about 1150° C. in a reducing atmosphere.

[0150] Preferably, after the wire drawing step, the surface of the wire after drawing is cleaned, and the wire is cross-wound onto a reel.

[0151] The above-mentioned drawing passes are cold passes.

[0152] Any other method known to a person skilled in the art for preparing the alloy of the present invention and for manufacturing the final product of the alloy may be used for this purpose.

[0153] The invention also relates to a method for manufacturing a component or a part of a component 1 made of the above alloy, such as Figure 2 As shown schematically, it includes:

[0154] Providing a filler wire of the above alloy; and

[0155] The component 1 or a part of the component is manufactured by a metal additive manufacturing process using a filler wire made of the above alloy and / or a powder of the above alloy as a filler material.

[0156] The component 1 or a part of the component is preferably a tool or a part of a tool for manufacturing an aerospace component made of a composite material, the composite material notably comprising an epoxy resin matrix in which reinforcing fibers in the form of carbon fibers are embedded. In particular, the component 1 is a mold or a part of a mold intended for manufacturing an aerospace component made of a composite material, the composite material notably comprising an epoxy resin matrix in which reinforcing fibers in the form of carbon fibers are embedded. For example, the component 1 defines a molding surface of a tool intended for manufacturing an aerospace component made of a composite material, and optionally also comprises a support structure for said molding surface.

[0157] For example, the above-mentioned additive manufacturing process is a type of additive manufacturing that uses an electric arc, a laser beam and / or an electron beam as energy sources to obtain fusion of the filler material.

[0158] In particular, the aforementioned additive manufacturing process is an additive manufacturing process known as directed energy deposition. With this method, the filler material is deposited, in particular through a nozzle, and is immediately melted by concentrated thermal energy, in particular by a laser beam, electron beam and / or electric arc.

[0159] For example, the additive manufacturing process is an arc wire, laser wire or electron beam wire (electron beam freeform manufacturing or electron beam additive manufacturing) process, or a hybrid additive manufacturing process combining arc wire and powder laser or arc wire and laser wire technology.

[0160] In the case of a hybrid additive manufacturing process combining arc wire and powder laser, or arc wire and wire laser technology, the powder and filler wire are made of the above alloys.

[0161] The above-mentioned additive manufacturing process is known per se and will therefore not be described in detail.

[0162] However, in the present invention, the above-mentioned additive manufacturing process includes several passes, each pass corresponding to the formation of a layer of the component 1 or a part of a component to be manufactured, and the time between two consecutive passes is determined by the shortest time required for the tool (in particular, the filling material melting tool, such as a laser beam, an electron beam and / or an electric arc) to return to the starting position of the deposition area.

[0163] In view of the above-mentioned advantageous properties of the alloy according to the invention, this manufacturing method allows the flexible production of high-quality components 1 or parts of components with high productivity, in particular with a deposition rate greater than or equal to 450 cm3 / h.

[0164] If the filler material comprises a powder, in particular in a hybrid process of arc wire and powder laser, before manufacturing the component 1 or a part of a component, the method further comprises a step of providing a powder of the alloy, such powder having a particle size between 20 μm and 150 μm after sieving, for example produced by plasma atomization of a wire made of the alloy, in particular having a diameter of about 3 mm.

[0165] The above-mentioned plasma atomization process is known per se and will therefore not be described in detail.

[0166] The invention also relates to a component 1 or a part of a component made of the above alloy, obtained by metal additive manufacturing.

[0167] The component 1 or a part of the component is preferably a tool or a part of a tool for manufacturing an aerospace component made of a composite material, the composite material particularly comprising an epoxy resin matrix in which reinforcing fibers are embedded in the form of carbon fibers. In particular, the component 1 is a mold or a part of a mold for manufacturing an aerospace component made of a composite material, the composite material particularly comprising an epoxy resin matrix in which reinforcing fibers are embedded in the form of carbon fibers. For example, the component 1 defines a molding surface of a tool for manufacturing an aerospace component made of a composite material, and optionally also includes a support structure for the molding surface.

[0168] The above metal additive manufacturing process, when using filler materials, particularly uses filler wires made of the above alloys and / or powders made of the above alloys.

[0169] For example, the above-mentioned additive manufacturing process is an additive manufacturing process that uses an electric arc, a laser beam and / or an electron beam as an energy source to obtain fusion of the filler wire.

[0170] In particular, the aforementioned additive manufacturing process is a method known as directed energy deposition, in which a filler material is deposited, in particular through a nozzle, and is immediately melted by concentrated thermal energy, in particular by a laser beam, electron beam and / or electric arc.

[0171] For example, the additive manufacturing process is an arc wire, wire laser or electron beam wire (electron beam freeform manufacturing or electron beam additive manufacturing) process, or a hybrid additive manufacturing process combining arc wire and powder laser or arc wire and laser wire technology.

[0172] If a hybrid additive manufacturing process combining arc wire and powder laser or arc wire and wire laser technology is used, the powder and filler wire are made of the above-mentioned alloys.

[0173] The component 1 or part of a component obtained by a metal additive manufacturing process is solidified. It therefore has a typical solidified microstructure of the nickel alloy in question, which generally comprises columnar dendrites obtained by mutual epitaxial growth and an orientation of the columnar dendrites that depends on the width and height of the metal walls constituted. In addition, the component 1 obtained by the additive manufacturing process presents, as a result of the process, a series of superimposed solidified layers. Each layer, formed by solidification of deposited molten metal droplets, melts the surface layer of the previous layer to create metallurgical continuity, thereby reheating the rest of the underlying layer. The further the layer considered is from the zone of melting and solidification, the lower its reheating temperature. This particular microstructure can be seen in the metallographic observation of the metallographic section of the component 1.

[0174] The component 1 or part of a component obtained by a metal additive manufacturing process can therefore be distinguished from components obtained by other methods, in particular from components obtained by conventional metallurgical methods that result in a recrystallized structure with homogeneous grains.

[0175] test

[0176] The inventors prepared in the laboratory under vacuum an alloy having the composition defined above, as well as a comparative alloy having a composition different from the above composition. Subsequently, these alloys were cast in the laboratory to obtain an ingot of truncated cone shape, having a diameter of 120 mm at the bottom of the cone and a diameter of 60 mm at the top of the cone. The obtained ingot was hot forged to obtain a rod with a diameter of 100 mm and a length of 500 mm, which was surface machined to remove the slag and then forged using a rotary forging machine sold by GFM to produce a rod with a diameter of 30 mm and a length of 3 meters. These rods were cold drawn to produce wires with a diameter of 5.5 mm and a length of 15 meters. The above-mentioned cold drawing step includes a plurality of consecutive drawing operations, and between each two consecutive drawing operations, a recrystallization heat treatment is carried out at a temperature of 1000°C for one hour. After cold drawing, the wire was annealed in a gas furnace at 1150°C for one hour, stripped and finally drawn on an industrial wire drawing machine to produce laboratory filler wire with a diameter of 1.2 mm wound on a 15 kg spool.

[0177] This production method is usually used in laboratories to produce filling wires, and can obtain filling wires having the same composition, surface cleanliness and performance as those obtained by the method for producing filling wires described above.

[0178] The alloy composition of each filler wire obtained is shown in Table 1 below.

[0179]

[0180]

[0181] Table 1: Composition of filler wire

[0182] In Table 1 above, alloys not having the composition of the present invention have been underlined.

[0183] In this table, "-" means that the element in question is present in trace amounts at most.

[0184] In all alloys, the balance is iron and impurities resulting from the production process.

[0185] Finally, using these wires, the inventors used arc additive manufacturing process and used a Fronius TPS500i welding station and a Yaskawa MH24 robot to manufacture the wall under the following manufacturing conditions:

[0186] Gas: Argon + 2.5% carbon dioxide; flow rate 18 L / min

[0187] Technology: CMT_Fronius

[0188] Collaboration: INVAR WAAM

[0189] Wire feeding speed: 8.6 m / min

[0190] Welding speed: 30 cm / min

[0191] Arc correction: -1.6

[0192] Dynamic correction: 6.2

[0193] Single track swing: amplitude 6 mm; frequency 2 Hz, pause 0.4 s at positions 1 and 3

[0194] Pause time between passes: 240 seconds

[0195] Pass increment: 2.5 mm

[0196] Deposition rate: 580 cm3 / h.

[0197] The wall obtained had a length of 150 mm, a width of 150 mm and a height of 70 mm.

[0198] For each alloy, the inventors determined the number of drops that occurred during the wall manufacturing process and the average thermal expansion coefficient of the alloy between 20°C and 200°C.

[0199] During the manufacturing process, the number of drops on the wall can be visually observed.

[0200] The average thermal expansion coefficient between 20°C and 200°C is measured as follows. The expansion ΔL of the alloy during heating from 20°C to 200°C is measured, and then the average thermal expansion coefficient α [20°C_200°C] between 20°C and 200°C is calculated using the following expression: Wherein ΔT=200°C-20°C, L0 is the initial length of the test piece (50 mm).

[0201] Table 2 summarizes the results of the tests using wire alloys No. 1 to No. 22 in Table 1 and Invar M93.

[0202]

[0203] Table 2: Results of wall fabrication tests using the alloys in Table 1

[0204] In Table 2 above, the test walls that did not conform to the invention have been underlined.

[0205] Tests conducted by the inventors have shown that walls made from filler wire of Invar M93 exhibit droplets and are therefore not satisfactory for the manufacture of tools or tool parts intended for the manufacture of composite aerospace parts at improved production rates (i.e., the relatively short interpass times employed during testing).

[0206] Alloys No. 1 to No. 4 in Table 1 above have a titanium and / or rare earth element content lower than the lower limit of the corresponding content range of the alloy of the present invention. The inventors found that the wall constructed from the wires made of these alloys also had a non-zero number of droplets, which were 7, 5, 3 and 1 respectively. Therefore, these alloys are also unsatisfactory for constructing tools or parts of tools intended for manufacturing composite aerospace parts with improved productivity.

[0207] Furthermore, it was observed that the average thermal expansion coefficient of alloy No. 1 between 20° C. and 200° C. was below the lower limit required for this application. The inventors believe that this insufficient average thermal expansion coefficient is due to the titanium content being below the lower limit of the alloy of the present invention.

[0208] Alloy No. 9 has a titanium content higher than the upper limit of the corresponding range of the alloy of the present invention. The wall does not show sagging. On the other hand, its average thermal expansion coefficient between 20°C and 200°C is 3.3×10 -6 ℃ -1 , which is too high for the considered application.

[0209] Alloys No. 10, No. 11, No. 14 and No. 18 have a cobalt content lower than -1.00 x Ni% + 36.80% and / or lower than 0.80 wt.%. Walls constructed from wires of these alloys do not sag. However, the average thermal expansion coefficients of these alloys between 20°C and 200°C are too high for the applications considered.

[0210] Alloys 16 and 21 have a cobalt content higher than -1.63×Ni content%+62.72%. Walls constructed from wires of these alloys show no sagging. However, the average thermal expansion coefficients of these alloys between 20°C and 200°C are 3.1×10 -6 ℃ -1 and 3.5×10 -6 ℃ -1 , which is too high for the considered application.

[0211] Alloy 22 has a cobalt content of more than 4.20 wt%. Walls constructed from wire of this alloy do not sag. However, the average thermal expansion coefficient of this alloy between 20°C and 200°C is 2.0×10 -6 ℃ -1 , which is too low for the considered application.

[0212] In contrast, the wall made of the alloys of the present invention (corresponding to compositions No. 5, No. 6, No. 7, No. 8, No. 12, No. 13, No. 15, No. 17, No. 19 and No. 20) did not sag. In addition, the average thermal expansion coefficient of these alloys between 20°C and 200°C was between 2.2×10 -6 ℃ -1 to 2.9×10 -6 ℃ -1 Thus, tools or parts of tools intended for manufacturing composite aerospace parts can be manufactured with improved productivity, ie with relatively short pass-to-pass times employed in testing.

Claims

1. An alloy for making a tool intended for use in the manufacture of an aerospace component made of a composite material, the alloy comprising, by weight: 32.6%≤Nickel≤38.0%; 0.80% ≤ Cobalt ≤ 4.20%, and: Cobalt ≥ -1.00×Ni%+36.80%, wherein Ni% represents the nickel content in the alloy in percentage by weight, and Cobalt ≤ -1.63×Ni%+62.72%, wherein Ni% represents the nickel content in the alloy in percentage by weight; 1.0%≤Titanium≤2.0%; 0.0010%≤Rare earth elements≤0.0500%; 0.10%≤Silicon≤0.35%; 0.15%≤Manganese≤0.60%; 0.005%≤Carbon≤0.04%; The balance is iron and impurities resulting from the production process.

2. The alloy according to claim 1, wherein The impurities generated by the production process include by weight: Calcium ≤ 0.0015%; Magnesium ≤ 0.0035%; Aluminum ≤ 0.0085%; Oxygen ≤ 0.0025%; Sulfur ≤ 0.0035%; Phosphorus ≤ 0.0100%; Boron ≤ 0.0005%; Molybdenum ≤ 0.1%; Chromium ≤ 0.1%; Copper ≤ 0.1%; Niobium ≤ 0.01%; Vanadium ≤ 0.01%.

3. The alloy according to claim 1 or 2, wherein The rare earth element includes yttrium, cerium, lanthanum, neodymium, praseodymium or a mixture thereof.

4. A filler wire made from an alloy according to one of claims 1 to 3.

5. A method for manufacturing the filling wire material according to claim 4, the method comprising the following steps: Providing a semi-finished product made of an alloy according to one of claims 1 to 3; thermally processing the semi-finished product to form an intermediate wire; and The intermediate filament is transformed into a filler filament having a smaller diameter than the intermediate filament, the transforming comprising a wire drawing step.

6. Use of an alloy according to one of claims 1 to 3 for producing at least a part of a tool intended for producing aerospace parts made of composite materials.

7. A component (1) or a part of a component made of an alloy according to one of claims 1 to 3.

8. The component (1) or part of a component according to claim 7, which is obtained by metal additive manufacturing.

9. Component (1) or part of a component according to one of claims 7 or 8, which component is a tool, in particular a mould, intended for the manufacture of an aerospace component made of composite material.

10. A method for manufacturing a component or a part of a component, comprising the step of manufacturing the component or the part of a component by a metal additive manufacturing process using a filler wire made of an alloy according to one of claims 1 to 3 and / or a powder of an alloy according to one of claims 1 to 3 as filler material.

11. The manufacturing method according to claim 10, wherein: The additive manufacturing process is selected from an arc wire process, a laser wire process, an electron beam wire process, and a hybrid additive manufacturing process combining arc wire and powder laser, or arc wire and laser wire technologies.

12. Use of the filler wire according to claim 4 as a filler wire in a metal additive manufacturing process.

13. Metal powder made from an alloy according to one of claims 1 to 3.

14. A method for manufacturing the metal powder according to claim 13, the method comprising the steps of: providing the filler wire according to claim 4, and plasma atomizing the filler wire to obtain the metal powder.

Citation Information

Cited By

  • Ultrahigh-strength steel wire material for rare earth magnesium composite additive manufacturing and preparation method of ultrahigh-strength steel wire material

    CN122214761A

  • A rare earth magnesium composite type ultra-high strength steel wire for additive manufacturing and a preparation method thereof

    CN122214761B